Hubungan antara Lingkar Pinggang dengan Nilai Volume Ekspirasi Paksa Detik Pertama (VEP ) dan Nilai Kapasitas Vital Paksa (KVP) pada Pemeriksaan Spirometri - ., Krisandi Hartanto (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Decreased lung function have been associated with cardiovascular disease and mortality. Studies have reported an impact ofcentral obesity on lung function among men. Waist circumference is one ofthe indicator for central obesity and is better than BMI and WHR inpredicting intra-abdominal fat. Obejctive: The aim of this research was toinvestigate the relationship between waist circumference with FEV valueand FVC value in men workers at the Central Office of PT. BankPembangunan Daerah Kalimantan Barat. Methods: This research was ananalytical study with cross-sectional design. A total of 41 subjects aged18-55 years were selected through a consecutive-sampling techniquebased on research criterias. Data were obtained from questionnairesabout subject’s smoking pattern, waist circumference (WC), body height,body weight and spirometry measurement. Subjects were grouped into 2categories, risk group (WC ≥ 90 cm) and non risk group (WC < 90 cm). Tindependenttest was used to analyze the data. Results: Mean waistcircumference was 91,61 ± 10,31 cm. Mean FEV and FVC values were 92,65 % and 93,77 % for non risk group and 85,50% and 84,21%. For risk group. FEV 1 1 and FVC values were significantly lower in risk group than in non risk group, there was statistically significant association between waist circumference with FEV values (p = 0,004) and FVC values (p < 0,001). Conclusions: Waist circumference is associated with FEV 1 value and FVC on spirometry measurement.Keywords: Waist circumference, spirometry, FEV, FVC.